Energy meteorology for accurate forecasting of PV power output on different time horizons. (September 2017) - Reindl, Thomas; Walsh, Wilfred; Yanqin, Zhan; Bieri, Monika
Abstract: Energy meteorology is a new discipline whose importance derives from the need for variable, non-dispatchable renewable power generation to be quantified on timescales from decades (resource assessment) down to minutes ("now-casting"). The need for power generation forecasts becomes more apparent as the variable generation fraction increases above a few percent – at this level sudden large changes in generation capacity ("ramp rates") can affect power quality and even lead to grid instability. For this reason, many jurisdictions worldwide are starting to implement forecasting requirements on solar photovoltaic (PV) plant owners, including China where the national standard GB/T 19964-2012 on "Technical requirements for connecting photovoltaic power stations to power systems" asks for 15-minute to day-ahead forecasts. Failure to do so or inaccurate predictions, i.e. outside of a desired corridor (±10-15%) lead to penalties in form of reduced reimbursements for the provided solar power. PV power output forecasting errors can arise not only from predicting irradiance, but also - and this is widely underestimated - from the conversion of irradiance to actual PV power generation. Additional uncertainties of ~10% during this step are not uncommon. In this paper, the economic value of forecasting is evaluated using a case study from Henan province, China. We show that even minor deviations from the requested forecasting frequency and prediction corridor can result in revenue losses that have direct impact on the financials of the project (i.e., discounted payback period, net-present value and internal rate of return). This will spark a growing need for accurate energy meteorology in the future.